Application of the SWAT model to assess climate and land use/cover change impacts on water balance components of the Kabul River Basin, Afghanistan - Jamal Hassan Ougahi; Shahid Karim; Syed Amer Mahmood (Journal of Water and Climate Change, 2022)
Hydrological models play a key role in simulating and assessing climate and land use/cover (LULC) change impacts on hydrology in a watershed. In this study, the impact of climate and LULC change was investigated using the Soil and Water Assessment Tool (SWAT) model. The simulated and observed streamflow showed a good agreement. Both Nash–Sutcliffe Efficiency (NSE) and coefficient of determination (R2) were found to be greater than 0.7 during the calibration (1985–2002) and validation (2003–2012) period. The water balance components were simulated with inputs from downscaled Global Climate Models (GCMs) data (i.e., future scenario (2030–2100) relative to a baseline period (1974–2004)) under RCP4.5 and RCP8.5, and hypothetical generated LULC change scenarios. All GCMs projected an increase in temperature over the Kabul River Basin (KRB), whereas there was a lack of agreement on projected precipitation among GCMs under both emission and future scenarios. Water yield (WYLD) and evapotranspiration (ET) were projected to decrease in the 21st century. Average annual WYLD was projected to increase under the agriculture-dominant scenario, whereas it decreased under forest and grassland-dominant scenarios. These results are valuable for relevant agencies and stakeholders to adopt measures to counter the negative impacts of climate and LULC change on water resources. HIGHLIGHTS The projected temperature consistently increases in the 21st century.; Most of the GCMs projected a decrease in annual and winter precipitation in the KRB.; The simulated water balance components show a higher impact by climate than LULC change scenarios.; The water yield was increased under the agriculture-dominant scenario, whereas it decreased under forest and grassland-dominant scenarios.;